Perbandingan Model Pembelajaran Learning Cycle 5E Dengan Model Tradisional Dalam Menigkatkan Kognitif Siswa - Ryzal Perdana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2019)
This study aims to 1) Know students' initial cognitive abilities in acid-base material, 2) Know students' cognitive enhancements in acid-base material, 3) Know the effectiveness of learning 5E Learning cycle in improving students' cognitive on acid-base material. Learning Cycle 5E learning model consists of 5 phases, namely Engagment phase, exploration, explaination, elaboration, and evaluation. Traditional learning models follow learning that is commonly used by teachers in everyday learning. This research is an experimental study with the number of samples in the experimental class using 30E learning cycle learning models as many as 30 students and control classes using traditional learning models of 30 students. The population in this study were all students of class XI SMA N 1 Pekalongan, Lampung. The sample in this study were students of Pekalongan 1 Public High School class XI IPA1 and XI IPA4 who had the same cognitive abilities. This study uses a quasi-experimental method with Non Equivalent (Pretest and Posttest) Control Group Design. The effectiveness of the 5E Learning Cycle learning model was measured based on the increase in students' cognitive abilities significantly. The results showed that the Learning Cycle 5E learning model was better at improving students' cognitive compared to Traditional methods. This can be seen from the average gain score of students' cognitive abilities for Traditional learning models and the 5E Learning Cycle Learning Model 0.53 and 0.65 respectively.